The Relationship Between Loneliness and Self-Discovery in Teenagers Using K-Pop Roleplayer Accounts on Twitter - Ramadhani, Nadya Vinansia; Wibowo, Doddy Hendro (International Journal Labs, 2023)
Teenagers fulfill social needs by communicating and relating well with other people. One of the media used to be used is Twitter. This research aims to determine the relationship between loneliness and self-disclosure in teenagers who use the K-Pop Roleplayer account on Twitter. The technique used in determining the sample was nonprobability sampling with purposive sampling. The subjects of this research were 100 K-Pop Roleplayer account users on Twitter. Data collection used a loneliness scale adapted from the Revised Loneliness Scale (UCLA Version 3), and a self-disclosure scale adapted from the Revised Self Disclosure (RSDS). The results of this research show that the correlation coefficient value is –0.181 with a significant value of 0.72>0.05. That means loneliness does not have a significant relationship with self-disclosure among teenagers using the K-Pop Roleplayer account on Twitter. This research can provide a reference for teenagers using K-Pop Roleplayer accounts on Twitter to maximize their use of Twitter according to their needs.